Consistent findings in glycaemic control, body weight and hypoglycaemia with iGlarLixi (insulin glargine/lixisenatide titratable fixed‐ratio combination) vs insulin glargine across baseline HbA1c, BMI and diabetes duration categories in the LixiLan‐L trial. Issue 10 (8th June 2017) - Wysham, Carol; Bonadonna, Riccardo C.; Aroda, Vanita R.; Puig Domingo, Manuel; Kapitza, Christoph; Stager, William; Yu, Christine; Niemoeller, Elisabeth; Souhami, Elisabeth; Bergenstal, Richard M.; ,
Abstract : Aims: To assess the impact of baseline characteristics on clinical outcomes in the LixiLan‐L trial, a randomized open‐label trial designed to evaluate the efficacy and safety of iGlarLixi, a novel fixed‐ratio combination of insulin glargine 100 U (iGlar) plus lixisenatide, in comparison with iGlar over 30 weeks in a population of patients with type 2 diabetes mellitus (T2DM) inadequately controlled on a previous regimen of basal insulin alone or in combination with 1 or 2 oral glucose‐lowering drugs. Materials and Methods: In this exploratory analysis of LixiLan‐L ( N = 736), efficacy outcomes were assessed within population subgroups derived from the following baseline characteristics: glycated haemoglobin [HbA1c; <8%, ≥8% (<64, ≥64 mmol/mol)]; duration of T2DM (<10, ≥10 years); body mass index (<30, ≥30 kg/m 2 ). Furthermore, the incidence of symptomatic hypoglycaemia with plasma glucose ≤3.9 mmol/L (≤70 mg/dL) was also analysed according to the same subgroups. Results: Compared with the iGlar treatment group, patients treated with iGlarLixi showed consistently greater reductions in HbA1c during the treatment period, with higher percentages of patients achieving the HbA1c target level of <7% (<53 mmol/mol) in all of the subpopulations tested ( P < .0001 for all), having consistent mitigation of body weight gain and with no major differences in the incidence of hypoglycaemia. Conclusions: iGlarLixi consistently improved glycaemic control compared with iGlar in all baseline characteristic subgroups of patients with T2DM inadequately controlled with insulin, including difficult‐to‐treat subgroups of patients with long duration of diabetes, obesity and high HbA1c. Clinical trial number: NCT02058160 (clinicaltrials.gov ).